Examining the Benefits and Barriers of Instructional Gardening Programs to Increase Fruit and Vegetable Intake among Preschool-Age Children. (21st May 2017) - Davis, Kristen L.; Brann, Lynn S.
Abstract : Research exists on using instructional gardening programs with school age children as a means of improving dietary quality and for obesity prevention. This article examines the potential use of instructional gardens in childcare settings to improving fruit and vegetable intake in young children. A qualitative study was conducted with childcare providers. Participants (n = 20 ) were recruited via e-mails, letters, and follow-up phone calls. Interviews were recorded, transcribed, and coded to identify themes within two areas( 1 ) childcare providers perceptions of children's fruit and vegetable consumption and( 2 ) components necessary to initiate or improve instructional gardening programs. Themes associated with provider's perceptions of child fruit and vegetable consumption included benefits of consumption, willingness to try fruits and vegetables, meeting recommendations, and influence of the home and childcare environments on child eating. Benefits, barriers, and resources needed were identified as themes related to starting or improving instructional gardening programs. Benefits to gardening with preschoolers are consistent with those found in school-age populations. While several barriers exist, resources are available to childcare providers to address these barriers. Increased knowledge and awareness of resources are necessary to improve the success of gardening programs in the childcare setting with the goal of improving child diet quality.